USING GEOGEBRA IN TEACHING PLANE VECTOR - Tommy Tanu Wijaya (IKIP Siliwangi, 2020)
The study of geometry knowledge is an important component of high school mathematics. Plane geometry is the main thread that runs through high school geometry knowledge. Vector learning is the focus and difficulty of plane geometry. When students encounter a new knowledge, it will be difficult to overcome it, and it is difficult to form a new logical system in their minds. Therefore, when students learn the content of vectors, they will have cognitive conflicts at different levels of thinking. The calculation from planar geometry to directed line segments needs a transition. It is difficult to understand the concept and nature of vectors without the help of teachers. This study attempts to guide the application of Geogebra software in teaching plane vector by using Van Hill Theory to intuitively display abstract geometric knowledge, and guide students to perform dynamic operations and deductive reasoning , Gradually help students transition from point to surface to vector operation, improve classroom teaching efficiency, and thereby optimize geometry teaching, in order to provide some reference for front-line teachers.